La bioluminiscencia como herramienta para evaluar el lavado de manos durante la formación de profesionales relacionadas con la Salud Pública - Contreras, Sara (2020)
Health Care Associated Infections (HAS), Foodborne Illness and zoonoses generate high costs for public health. A simple and inexpensive measure, and with evidence of its effectiveness in their prevention is handwashing, a protocol established by the World Health Organization (WHO), that is taught in professional training programs to students of human and animal health, as well as those who process food. The aim of this descriptive and cross-sectional study was to evaluate handwashing by bioluminescence in students during their performance in practice centres, as well as their knowledge and attitude towards handwashing, by a survey involving 45 students from the Gastronomy, Nursing and Veterinary Medicine in their last cycle of academic training of a private higher education institution (Concepción, Chile). The students showed an adequate knowledge of handwashing (90%), but a bad attitude towards it (70% of favourable responses). Students gave greater importance to handwashing when they are observed, evaluated or when their classmates do it, showing a lack of awareness regarding the importance of doing it. The bioluminescence test indicated a significant reduction between before and after handwashing, from 2951±40 URL vs. 400.7±73 URL, respectively (p<0.0001), without significant differences between the careers. The measurement of ATP by bioluminescence is a simple and rapid method to evaluate the effectiveness of handwashing, being a tool that can be incorporated into disciplinary training in careers directly related to human-animal health.